(3eaJGM GdcfR GdCaNQ def CQGO Cf jUd Edi GdZfj GdCcHQs - (3GdbGhbLj GdWQGHdSj GdMfaj, CHh GdeMGSf, eMeO Hf Ndjd Hf EHQGgje, J(B1305(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd GdUdGI Ydi MHjHg eaJGMG dcd HGHhHYO ajbhdeMeO Hf Ndjd GdHTHTdeG cGfJ GdUdGI Ydi GdfHj Udi Gddg Ydjg hSde SHHG deYJca GdMVQGJ GdQHGfjIs
(3BNQgG (B:s
(3ef GdMVQGJ GdeUWajI eSJZQbG aj GdHMGQ ef ZjQ eGfY hdG YGFb hdG MLGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 118s
(3eYLe GdeDdajf(B: 3 / 278s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs